Agama dan Tradisi: Pergumulan Bissu’ Masyarakat Bugis di Sulawesi Selatan - Nurul Azizah (JURNAL PENELITIAN KEISLAMAN, 2022)
Pre-Islamic South Sulawesi society recognizes five categorizations based on gender, namely burane (male), makkunrai (female), calabai (men who dress like women), calalai (women who dress like men) and bissu' (women who dress like men). neither male nor female). Bissu' categorizes theirself as a human being who is neither male nor female. In pre-Islamic belief, they occupied an important position as a liaison between the king and God. They lead various rituals and also have supernatural powers. This article shows the shift in bissu' position after the entry of Islam in South Sulawesi in the 16th century. The dominance of Islam then led to the assimilation process, bissu' changed its position no longer as part of belief but into culture. Furthermore, to maintain their existence, the bissu' wear Islamic symbols and make calabai categories to distinguish themselves from those who are considered incompatible with Islamic values.